Role of anisotropy in the spin-dimer compound BaCuSi2O6 - Sebastian, SE; Tanedo, P; Goddard, P; Lee, S; Wilson, A; Kim, S; Cox, S; McDonald, R; Hill, S; Harrison, N; Batista, C; Fisher, I (2006)
We present results of magnetization and electron paramagnetic resonance experiments on the spin-dimer system BaCu Si2 O6. Evidence indicates that the origin of anisotropic terms in the spin Hamiltonian lies in magnetic dipolar interactions. Axial symmetry breaking is on a very small energy scale of ≤11 mK, confirming Bose-Einstein condensation critical scaling over an extended temperature range in the vicinity of the quantum critical point. © 2006 The American Physical Society.